A Comparative Analysis of Rural versus Urban Preschool Children's Sugar-Sweetened Beverage Consumption, Body Mass Index and Parent's Weight Status. (March 2022) - Montgomery, Michele; Johnson, Paige; Ewell, Patrick
Background: Childhood overweight and obesity continues to be a major public health concern, especially in minority, low-income, and rural populations. In order to develop health promotion interventions aimed at reducing obesity rates, there is a need to identify which populations have the highest rates of obesity and the risk factors associated with these high rates. Methods: Data collected from low-income, preschool children and their parents in an urban community and a rural community in Alabama were analyzed and compared. Body Mass Index (BMI) was collected during school based health screenings, and information regarding parent's BMI and child's consumption of sugar-sweetened beverages (SSBs) were collected by parent report. Results: Of the 363 children screened, 12.8% (15.2% rural and 11.9% urban) were considered overweight, and 15.8% (20.2% rural and 14.2% urban) of the sample was classified as obese. Rates of overweight and obesity for mothers were 27.6% (25.3% rural and 28.4% urban) and 48% (56.3% rural and 44.8% urban) respectively and 39.6% (53.3% rural and 34.4% urban) and 34.6% (28.3% rural and 36.9% urban) for fathers. Parents reported their child consumed 3.82 SSBs per day. Overall, mother's BMI, father's BMI and sugar-sweetened beverage consumption was positively associated with child's BMI. However, there were no significant interactions between the rural and urban groups. Conclusion: Rates of overweight and obesity remain high in low-income, predominantly minority preschool children and their parents in two communities in Alabama. Consumption of SSBs, mother's BMI, and father's BMI are three factors impacting the weight status of low-income preschool children. These factors are significant in both rural and urban children.